Immune checkpoint molecule expression is altered in the skin and peripheral blood in vasculitis - Chie Miyabe (Nature Portfolio, 2021)
Abstract Dysfunction of immunoinhibitory signals and persistent T cell activation reportedly play important roles in the development of vasculitis. The skin is one of the most accessible organs, and it is suitable for the characterization of immune cell signatures. However, the inhibitory checkpoint molecules in the skin and their relevance to vasculitis have not been studied. Here, we investigated the profile of immune checkpoint molecules in the skin and peripheral blood of patients with vasculitis and healthy donors. We found that some of the inhibitory checkpoint molecules, including programmed cell death 1 receptor (PD-1), were elevated in T-cells in the blood of patients with systemic and cutaneous vasculitis. In addition, programmed death-ligand 1 (PD-L1) expression was elevated in the skin of patients with cutaneous vasculitis. Histologically, PD-L1 was highly expressed in the vessels in the skin along with CD4+ and CD8+ T-cell infiltration in patients with cutaneous vasculitis. Notably, plasma soluble PD-L1 levels were increased, and these correlated with C-reactive protein in patients with systemic vasculitis. Our findings suggest that inhibitory checkpoint molecules might be differentially modulated in the skin and peripheral blood of patients with vasculitis, and that the alteration of the PD-L1/PD-1 axis may be associated with the regulation of T-cell activation in vasculitis.